Tourism planning and development in Western Europe - Andriotis, Konstantinos; Pinto Cardoso, Carla; Stylidis, Dimitrios (Cabi regional tourism series, 2022)
"Focusing exclusively on tourism development, planning and policy, this book draws together new voices to provide case studies illuminating issues across western Europe. It adopts a range of methodological approaches to cover areas such as industrial tourism, natural and cultural heritage, and micro-destinations, and considers post-COVID tourism"--